Empowering leadership and achievement motivation in enhancing digital learning behavior: Mediating effects of learning climate - Trihantoyo, Syunu; Supriyanto, Achmad; Ghani, Muhammad Faizal Bin A.; Khamidi, Amrozi; Andari, Shelly (Edelweiss Applied Science and Technology, 2025)
Digital learning behavior in elementary school teachers is not fully relevant to the current portrait of digital competence. Research that comprehensively discusses the role of empowering leadership and achievement motivation, with learning climate mediation in shaping digital learning behavior, has not been widely conducted. The purpose of this study is to analyze the effect of empowering leadership on educational institution leaders and teacher achievement motivation, mediated by the learning climate, in fostering digital learning behavior in elementary schools in Surabaya City that implement emancipated learning programs. The research method uses a quantitative approach with multi-level analysis conducted in stages: (a) interclass correlation test to see the value of ICC (1), ICC (2), and RWg; (b) construct validity test and construct reliability test; (c) hypothesis testing is done with multi-level analysis and single-level analysis; and (d) coefficient of determination test. The results of this study show that empowering leadership and achievement motivation do not directly affect the learning climate or digital learning behavior. The variable that affects digital learning behavior is the learning climate. However, the learning climate does not play a role as a mediator in the tests conducted in this study. This study implies that it provides an overview of the focus of school leaders in fostering a learning climate, along with other factors that are more relevant to the development of school conditions, in addition to the variables that have been tested in this study.